Improvement of Electrical Power System Stability by using PSS-PID Based on Model Reference Adaptive Control Technology - ميهوب عمار; فيصل شعبان; نسمت أبو طبق (Latakia University Journal -Engineering Sciences Series, 2023)
signal oscillations are caused by electrical power system disturbances and eventually become dangerous if there is not enough means to dampen these oscillations. The power system stabilizer (PSS) provides additional damping for rotor oscillations by providing an additional control signal to the excitation circuit, but the effect of the vibration damper is due to several factors, the most important of which are How to adjust its parameters to achieve the maximum benefit, which is to return the system to a stable state after a disturbance within a record time, in order to maintain the reliability and stability of the electric power system. In this paper, we applied the model reference adaptive control technique to dampen the vibration of an power system with the aim of improving the stability of the small signal. The method is based on developing an appropriate reference model, based on the desired specifications that can be achieved through the system dynamics. And the use of a PID controller, where its parameters were obtained through the trial and error method along with an adaptive loop that uses the PID controller to track the performance of the reference model regardless of the operating conditions and system parameters. The effectiveness of the proposed control method has been tested on an unstable test system, which shows the effectiveness of this technique to dampen vibrations Power system over a wide range of unstable operating conditions and turbulent system models.